Effect of occupational exposures on lung cancer susceptibility: a study of gene-environment interaction analysis - Malhotra, Jyoti; Sartori, Samantha; Brennan, Paul; Zaridze, David; Szeszenia-Dabrowska, Neonila; Świątkowska, Beata; Rudnai, Peter; Lissowska, Jolanta; Fabianova, Eleonora; Mates, Dana; Bencko, Vladimir; Gaborieau, Valerie; et al. (Cancer epidemiology, biomarkers & prevention, 2015)
BACKGROUND: Occupational exposures are known risk factors for lung cancer. Role of genetically determined host factors in occupational exposure-related lung cancer is unclear. METHODS: We used genome-wide association (GWA) data from a case-control study conducted in 6 European countries from 1998 to 2002 to identify gene-occupation interactions and related pathways for lung cancer risk. GWA analysis was performed for each exposure using logistic regression and interaction term for genotypes, and exposure was included in this model. Both SNP-based and gene-based interaction P values were calculated. Pathway analysis was performed using three complementary methods, and analyses were adjusted for multiple comparisons. We analyzed 312,605 SNPs and occupational exposure to 70 agents from 1,802 lung cancer cases and 1,725 cancer-free controls. RESULTS: Mean age of study participants was 60.1 ± 9.1 years and 75% were male. Largest number of significant associations (P ≤ 1 × 10(-5)) at SNP level was demonstrated for nickel, brick dust, concrete dust, and cement dust, and for brick dust and cement dust at the gene-level (P ≤ 1 × 10(-4)). Approximately 14 occupational exposures showed significant gene-occupation interactions with pathways related to response to environmental information processing via signal transduction (P < 0.001 and FDR < 0.05). Other pathways that showed significant enrichment were related to immune processes and xenobiotic metabolism. CONCLUSION: Our findings suggest that pathways related to signal transduction, immune process, and xenobiotic metabolism may be involved in occupational exposure-related lung carcinogenesis. IMPACT: Our study exemplifies an integrative approach using pathway-based analysis to demonstrate the role of genetic variants in occupational exposure-related lung cancer susceptibility. Cancer Epidemiol Biomarkers Prev; 24(3); 570-9. ©2015 AACR.
Keywords: Male; nádory plic; Risk Factors; Occupational Exposure; Genotype; Occupational Diseases; Lung Neoplasms; signální transdukce; nemoci z povolání; pracovní expozice; Europe; Genome-Wide Association Study; Case-Control Studies; mužské pohlaví; jednonukleotidový polymorfismus; Signal Transduction; Evropa; Polymorphism, Single Nucleotide; lidé; ženské pohlaví; studie případů a kontrol; interakce genů a prostředí; Humans; rizikové faktory; Gene-Environment Interaction; genotyp; Female; lidé středního věku; celogenomová asociační studie; Middle Aged